Pathways of Patients at the Grahamstown Lunatic Asylum, 1890 to 1907 - Rory du Plessis (Pretoria University Law Press (PULP), 2020)
Pathways of patients explores the casebooks of the Grahamstown Lunatic Asylum during the superintendence of Dr Thomas Duncan Greenlees, from 1890 to 1907. The hallmark of Pathways of patients is an examination of the asylum's casebooks to bring into view the humanity of the patients, their distinct personal experiences, and their individuality. The book is underpinned by an allied goal to retrieve the casebook narratives of the patients' life stories, their acts of agency, and their pathways to and from the asylum, with a view to understanding and portraying the context of patient experiences at the time.